Observations on the water quality management of larval and postlarval rearing tanks of Penaeus monodon hatchery at Cox’s Bazar, Bangladesh - Das, N G; Sarwar, S M M; Parvez, M M (Indian Journal of Fisheries, 2011)
The present study was carried out in the Pioneer Hatchery Ltd. situated at Cox’s Bazar sea coast of southeastern apex of Bangladesh. Water parameters such as temperature, salinity, dissolved oxygen, pH etc. greatly influence the larval and Jlostlarval development and their survival rate in the rearing tanks of Penaeus monodon hatchery. For quality assessment water samples were collected fimr times daily from the larval and postlarval rearing tanks and measured the water temperature, salinity, DO, pH, H2S, NH3-N, N02-N, N03- N, P04-P, Si02 â€¢ The results of analysis of these parameters have been critically evaluated to find out their optimal range in the hatchery management of Penaeus monodon.